Gender and nursing in Portugal: the focus on men's double status of dominant and dominated - Santos, M. H. (2019)
This article presents a study that sought to identify the gender dynamics prevailing in a health-related context of tokenism - nursing - in which the members of a dominant group in society - men - are proportionally scarce. Specifically, this study aimed to consider how men experience their integration into a feminized profession. Furthermore, the individual experiences and professional dynamics were placed in perspective with the results of other studies focusing on male populations in high-status professions, in particular medicine, to analyse the intersectionality of status and power. This study involved individual, semi-structured interviews with twelve male nurses, aged between 40 and 58 years, from across the six existing nursing specialties in Portugal. Analysis of the results, obtained through the Alceste software and thematic study carried out according to the social constructionist perspective in gender studies, indicates that tokenism dynamics interweave a double power asymmetry: the professional asymmetry between male doctors and male nurses, and the gender symbolic asymmetry between men and women. In the nursing profession, this double asymmetry proves beneficial to male nurses.